2019
DOI: 10.1111/soc4.12699
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the Nordic paradox: A review of qualitative interview studies on intimate partner violence against women (IPVAW) in Sweden

Abstract: Intimate partner violence against women (IPVAW) is a major public health problem in countries around the world, including the Nordic region. Contrary to what would be expected, as the Nordic countries are rated among the most gender equal in the world, survey data suggests that the lifetime prevalence rates of IPVAW in Sweden and neighboring Nordic countries are among the highest in the EU. This phenomenon, which has been termed the Nordic paradox, requires elucidation. The aim of this review is to explore wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 88 publications
(314 reference statements)
2
32
0
Order By: Relevance
“…Studies are needed to understand whether this is driven by methodological or reporting biases (e.g., women in more equitable countries may be more forthcoming about IPV victimization) or whether there are other factors that could explain this contradictory pattern. Based on a review of qualitative studies with victims, perpetrators, and service providers, Wemrell et al () put forth the argument that discourse around gender equality in Sweden may obscure continuing power dynamics that disadvantage women. Thus, there may be some disconnect between policies supporting gender equity and actual practices that reinforce gendered power imbalances.…”
Section: Community and Sociocultural Contextsmentioning
confidence: 99%
“…Studies are needed to understand whether this is driven by methodological or reporting biases (e.g., women in more equitable countries may be more forthcoming about IPV victimization) or whether there are other factors that could explain this contradictory pattern. Based on a review of qualitative studies with victims, perpetrators, and service providers, Wemrell et al () put forth the argument that discourse around gender equality in Sweden may obscure continuing power dynamics that disadvantage women. Thus, there may be some disconnect between policies supporting gender equity and actual practices that reinforce gendered power imbalances.…”
Section: Community and Sociocultural Contextsmentioning
confidence: 99%
“…However, this fact contradicts the Nordic Paradox, which reveals that countries with a very high score in the Equality Index (EIGE, 2019) such as Sweden (83.6 points), Finland (73.6 points) and Denmark (77.5 points) have higher levels of GV than other EU countries. No determining explanation has been found for why this is the case (Gracia, Martín-Fernández, Lila & Ivert, 2019;Gracia and Merlo, 2016;Wemrell et al, 2019) but the relationship between hostile sexist attitudes and GV has been demonstrated (Juarros-Basterretxea, Overall, Herrero & Rodríguez-Díaz, 2019). Hostile sexist attitudes also influence health professionals who have a lower level of involvement in identifying women who are victims of GV in their workplace (Noriega, Juarros-Basterretxea & Herrero, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This search was restricted to the title and subject of publications. The work proceeded with the reading of abstracts, keywords and the complete content of the publication, when necessary, to construct the theoretical framework exposed in this article, thus constituting a systematic bibliographic analysis of publications (Sampaio & Mancini, 2007;Wemrell, 2019). In this context, the systematic review uses as a data source the publications related to a certain theme (Wemrell, 2019), thus providing a summary -of the evidence related to a specific intervention strategy, through the application of explicit and systematic search methods, critical thinking and synthesis of selected information‖ (Sampaio & Mancini, 2007 p. 84).…”
Section: Methodsmentioning
confidence: 99%